Regional Apparatus Resource Readiness Through Digitalization of Public Programs and Services Towards Smart City (Study at Regional Education and Training Personnel Agency South Halmahera Regency ) - Haryono A. Hi. Gani; Ali Lating; Syarifuddin Usman (JOURNAL OF ETHNIC DIVERSITY AND LOCAL WISDOM, 2023)
Nowadays, almost all cities in every developed country have implemented the Smart City concept by utilizing information and communication technology (ICT) to be able to control all the resources in the city. Indonesia is one of the countries implementing this smart city, including DKI Jakarta, Surabaya, Bandung, Yogyakarta and Makassar. In the government program on "Movement Towards 100 Smart Cities" as many as 146 districts/cities have developed smart cities. One of the districts in North Maluku Province is Halmahera Seatan Regency. However, referring to BPS data regarding the human development index (HDI) in South Halmahera Regency in 2021 it is still low. The obstacle is whether with the availability of these technological facilities, can the community and the relevant government, in this case regional officials, be able to implement these online-based services. The aim of this research is to determine the readiness of the South Halmahera Regency Regional Government and improve the quality of regional apparatus resources towards a Smart City. The type of research used in this research is descriptive qualitative. Meanwhile, data collection techniques include observation, interviews and documentation. As well as using data analysis techniques in this research, the Miles and Huberman model of data analysis techniques, namely data reduction (data reduction), data presentation (data appearance), and drawing conclusions (drawing conclusions/verification). Based on the research results, it shows that the Regional Education and Training Personnel Agency (BKPPD) of South Halmahera Regency has improved the human resources of regional officials through digitalization programs and community services towards Smart City. However, there are obstacles that stand in the way of improving regional apparatus human resources, namely inadequate facilities, limited budgets, and also many regional employees who are not yet skilled in operating technology due to age and other factors. This greatly influences the process of improving the quality of reliable apparatus human resources. . Keywords: , , ,